A Bad Deal: British Columbia's Emphasis on Deterrence and Increasing Prison Sentences for Street-Level Fentanyl Traffickers Vulnerable Populations: Delay, Sentencing and Removal - Hrymak, Haley (Manitoba Law Journal, 2018)
Disclaimer: This summary was generated by AI based on the content of the source document.